Role of Laparoscopy in Detecting Pelvic Causes of Female Subfertility in Obstetrics and Gynaecology Department - Maryam Yasmin, Maria Pervez, Maria Iqbal, Amna Begum, Asghar Ali Memon, Aqsa Latif (Pakistan Journal of Medical & Health Sciences, 2024)
Background: laparoscopy is one of the diagnostic technique that provides details on the state of the ovaries and fallopian tubes, as well as any abnormalities in the uterus. Objective: the aim of this study was to determine the Role of laparoscopy in detecting pelvic causes of female subfertility in obstetrics gynaecology Material and Method: The present cross-sectional descriptive study was carried out at the department of gynaecology Lady Reading hospital Peshawar from January 2023 to June 2023 after taking permission from the research team of the hospital. Volunteers’ women of different age groups (ranged 40 -80 years) with trouble to become pregnant or subfertility were included while individuals with heart diseases, stomach problems and those who had not lived together for a minimum of 12 months were excluded. We used consecutive sampling without probability to include people in a sequential fashion without using a random selection process. After being fully informed about the study, the participants voluntarily decided to take part and gave their express consent. We determined the required number of participants using free WHO software. The sample size determines was 191. Results: A total of 191 women were enrolled in this study. The mean age of the study participants was 29.61± 6.904 years. The mean duration of the marriage was 7.13 ±1.265 years and the length of the subfertility was 5.57± 3.1. 96(50.2%) females had primary subfertility and 95(49.7%) had secondary subfertility. The most frequent cause of infertility was polycystic ovarian syndrome in 42 cases (21.9%), followed by PID in 35 cases (18.3%), tubal occlusion in 30 cases (15.7%), endometroitic deposits in 27 cases (14%), ovarian cysts in 25 cases (13%), peritubal and peri-ovarian adhesions in 10 cases (5.2%), and fibroids in 2 cases (1.0%) of females. However, in 20 (10.4%) of the females during laparoscopy showed no cause. Conclusion: The present study concluded that for women with a history of pelvic inflammatory disease (PID), pelvic surgery, and chronic pelvic pain, early consideration of laparoscopy is recommended in order to make the best treatment choices. Keywords: Laparoscopy; Pelvic; Female; Subfertility